Preparation of Media Object Presentation and Sensory Effect Rendering in Mulsemedia Applications - Josué, Marina; Muchaluat-Saade, Débora; Moreno, Marcelo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
Nowadays multimedia applications are employed in different fields as entertainment, education, government services, health and e-commerce. Moreover, some applications incorporate sensory effects along with traditional multimedia content, stimulating other human senses beyond sight and hearing to convey information. Those applications are called mulsemedia applications, where the maintenance of synchronization among media objects and sensory effects is a key point for user quality of experience. In order to minimize delays or failures on content reproduction, this paper proposes a new operation on media objects and sensory effects that can be offered to authors of mulsemedia applications. This operation enables the preparation of media object presentation or the preparation of sensory effect rendering, considering device limitations on which the application will be executed. As proof of concept, our proposal is implemented on multimedia applications using the NCL language, through specification of a new NCL event type, named preparation event. Furthermore, a new NCL media property is presented, allowing the control of continuous media reproduction. Finally, three use cases are defined to demonstrate the use of the preparation event in multimedia and mulsemedia applications